2020
DOI: 10.1096/fj.202001562r
|View full text |Cite
|
Sign up to set email alerts
|

Occludin, caveolin‐1, and Alix form a multi‐protein complex and regulate HIV‐1 infection of brain pericytes

Abstract: Pericytes are multifunctional mural cells that surround microvessels and are often in direct cellular contact with endothelial cells. 1,2 They cover 30% of the abluminal surface of endothelial cells in peripheral capillaries 3 and over 90% of brain capillaries. 4 By coordinating functions with endothelial cells, neurons, and astrocytes, pericytes have recently attracted significant attention for regulating the development, functional integrity, and the maintenance of blood-brain barrier (BBB). 5-8 In addition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(50 citation statements)
references
References 70 publications
7
43
0
Order By: Relevance
“…Primary human brain astrocytes, pericytes and human microglia were infected with HIV-1 for 24h and 48h and the expression levels of HIV-1 gag were measured by qPCR. In agreement with previous studies, we found a successful infection of HIV-1 in microglial cells (50,51), pericytes (55)(56)(57), and astrocytes (52)(53)(54). There was signi cantly higher expression of HIV-1 gag 24h after infection compared to 48h in microglia, pericytes, and to a lesser degree in astrocytes (Fig.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Primary human brain astrocytes, pericytes and human microglia were infected with HIV-1 for 24h and 48h and the expression levels of HIV-1 gag were measured by qPCR. In agreement with previous studies, we found a successful infection of HIV-1 in microglial cells (50,51), pericytes (55)(56)(57), and astrocytes (52)(53)(54). There was signi cantly higher expression of HIV-1 gag 24h after infection compared to 48h in microglia, pericytes, and to a lesser degree in astrocytes (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…EC were excluded from these analyses because no productive HIV-1 infection in EC has been reported (60). The results indicated that astrocytes, pericytes, and microglia are susceptible to HIV-1 infection, con rming literature reports (51,55,56,58). In addition, HIV-1 Gag RNA levels were signi cantly higher 24h after infection when compared to 48h after infection in all three cell types (Fig.…”
Section: Cells Of the Nvu Are Susceptible To Hiv-1 Infectionsupporting
confidence: 80%
See 3 more Smart Citations